Hyaline Membrane Disease in Preterm Newborn - Andrieta Berliana Marzani; Angelica Rosa Septiana Hartono; Chris Monalisa; Cindy Thalia Putri; Jessica Natasya Caesaria; Kevin Axel Laurent Susanto; Novinka Iriane; Sheila Meriyani; Zarahnaya Putri Dwicahyani; Mathias Rusli; Wawan Kustiawan (Medical Clinical Update, 2022)
Hyaline membrane disease (HMD) is commonly found in preterm infants. This disease occurs as the result of surfactant deficiency due to prematurity. Surfactant deficiency results in increased alveolar surface tension, with resistance to inflation and alveolar collapse at the end of expiration. As a result, the alveoli are injured due to shear stresses on the alveolar walls. The injury could be seen in chest x-ray, as the most common radiological modality to help differentiate diagnosis. Plain chest x-ray findings of HMD are low lung volumes, diffuse, bilateral and symmetrical granular opacities, bell-shaped thorax, and air bronchograms. This case study showed chest x-ray finding of preterm newborn that diagnosed with respiratory distress syndrome clinically.